2002
DOI: 10.1246/bcsj.75.1255
|View full text |Cite
|
Sign up to set email alerts
|

Selective Synthesis, Characterization, and Configurational Flexibility of the Coordinatively Unsaturated Metal Center of Half-Sandwich Type Complexes with the Less-Hindered Hydrotris(3, 5-dimethyl-4-X-1-pyrazolyl)borate Ligands [TpMe2,XMII(κ2-O,O′-L)] (M = Ni, Co; L = NO3, OAc; X = Me, H, Br)

Abstract: The selective synthesis of half-sandwich type complexes of Ni(II) and Co(II) with the less-hindered hydrotris(3,5-dimethyl-4-X-1-pyrazolyl)borate [X = Me (TpMe3; a series), H (TpMe2; b series), and Br (TpMe2,Br; c series)] ligands, [TpMe2,XMII(κ2-O,O′-L)] [L = NO3 (2), OAc (3)], has been achieved by dropwise addition of a THF solution of NaTpMe2,X to an excess amount of ML2 dissolved in MeOH. The solid state structures of the nitrato complexes 2 have been characterized by X-ray crystallography as their solvate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…For Tp* complex 1 , its CH 2 Cl 2 solution showed moderate-intensity ( ε ≈ 80 M –1 cm –1 ) absorption around the 500–570 nm region, whereas the MeCN solution revealed weakened absorption ( ε ≈ 40 M –1 cm –1 ) around the 480–550 nm region. This changing spectral behavior was similar to that observed for the previously reported Tp Me3 ligand complex [Co II ( к 3 -NO 3 )( к 3 -Tp Me3 )] [ 25 ]. In the MeCN solution, these Tp Me2,X complexes turned to the corresponding solvated hexa-coordinated Co(II) species as found in the crystal structure (see Figure 1 and Scheme 2 ).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…For Tp* complex 1 , its CH 2 Cl 2 solution showed moderate-intensity ( ε ≈ 80 M –1 cm –1 ) absorption around the 500–570 nm region, whereas the MeCN solution revealed weakened absorption ( ε ≈ 40 M –1 cm –1 ) around the 480–550 nm region. This changing spectral behavior was similar to that observed for the previously reported Tp Me3 ligand complex [Co II ( к 3 -NO 3 )( к 3 -Tp Me3 )] [ 25 ]. In the MeCN solution, these Tp Me2,X complexes turned to the corresponding solvated hexa-coordinated Co(II) species as found in the crystal structure (see Figure 1 and Scheme 2 ).…”
Section: Resultssupporting
confidence: 88%
“…Tp* complex 3 had already been reported as an analogue of a penta-coordinated iron(II) complex [Fe(Tp*)(L Ph )], which showed O 2 -binding capability to yield the corresponding mononuclear iron(III)-superoxo compound [ 18 ]. In the original report, 3 had been obtained from a cobalt(II)-acetato complex, [Co(Tp*)( к 2 -OAc)] [ 25 ]. As described in the previous report, the molecular structure of 3 had been revealed by X-ray crystallography.…”
Section: Resultsmentioning
confidence: 99%
“…Figure S8 (the Supportingi nformation) shows that nitrite, nitrate, and triflate derivatives of 6 also contain fivefold coordinated Co II ,a sc onfirmed by comparison to the literature-known complex [Tp*Co(OAc)]. [28] Nitrite is an interesting case since it is known to coordinate either in monodentate (nitro-, by the Natom) or bidentate (nitrito-, by two oxygen atoms) fashion. The nitrito-to-nitro linkagei somerization has been extensively studied for Co III [29] and it has been found that the nitro-form is more stable.…”
Section: Uv/vis-nir Spectramentioning
confidence: 75%
“…[ Tp*Co(OAc)] was prepared according to the literature procedure. [28] Fourier transform infrared (FTIR) spectra were recorded with an ATRu nit in the range 4000-180 cm À1 on aB ruker Equinox 55 FTIR spectrometer.D iffuser eflectance UV/Vis-NIR spectra were recorded in the range 2000-250 nm on aP erkinElmer l 750 ss pectrometer equipped with aL absphere 60 mm RSA ASSY integrating sphere with 08/d measuring geometry.L absphere Spectralon SRS-99 was used as aw hite standard. Thermogravimetric analyses (TGA) were performed with aT AI nstruments Q500 analyzer in the temperature range of 25-900 8Ci n flowing nitrogen gas at the heating rate of 5Kmin À1 .T G/MS measurements were performed with the same instrument combined with the Hiden QIC-20 gas analysis system.…”
Section: General Proceduresmentioning
confidence: 99%
“…Labile "half-sandwich-type" com-plexes, [Ni II (Y)(Tp iPr2,Br )] (Y denotes mononegative ligand, such as nitrate (1 a), acetate (1 a'), and chloride (1 a # )), were synthesized successfully by the metathesis of NaTp iPr2,Br and the corresponding nickel(II) salts (Ni II Y 2 ). [10] In contrast to less hindered Tp Me2,X -ligands system, [11] undesired homoleptic complex [Ni II A C H T U N G T R E N N U N G (Tp R ) 2 ] did not form in this hindered Tp iPr2,Br -ligand system. The molecular structure of an acetonitrile adduct of the nitrate complex, [Ni II…”
Section: Synthesis Of Nickel(ii) Complexes With Tp Ipr2brmentioning
confidence: 98%